An infectious progenitor for the murine IAP retrotransposon: Emergence of an intracellular genetic parasite from an ancient retrovirus - Ribet, David; Harper, Francis; Dupressoir, Anne; Dewannieux, Marie; Pierron, Gérard; Heidmann, Thierry (Genome Research, 2008)
Mammalian genomes contain a high load of mobile elements among which long terminal repeat (LTR)- retrotransposons may represent up to 10% of the genomic DNA. The murine intracisternal A-type particle (IAP) sequences, the prototype of these mammalian “genetic parasites,” have an intracellular replicative life cycle and are responsible for a very large fraction of insertional mutagenesis in mice. Yet, phylogenetic analyses strongly suggest that they derive from an ancestral retrovirus that has reached the germline of a remote rodent ancestor and has been “endogenized.” A genome-wide screening of the mouse genome now has led us to identify the likely progenitor of the intracellular IAP retrotransposons. This identified “living fossil”—that we found to be present only as a single fully active copy—discloses all the characteristics of a bona fide retrovirus, with evidence for particle formation at the cell membrane, and release of virions with a mature morphology that are infectious. We show, by generating appropriate chimeras, that IAPs derive from this element via passive loss of its env gene, and gain of an endoplasmic reticulum targeting signal, resulting in its “intracellularization” and in the gain of transpositional activity. The identification within the mouse genome of the still active retroviral progenitor of the IAP endogenous mobile elements and the experimental dissection of the molecular events responsible for the shift in its life cycle provide a conclusive illustration of the process that has led, during evolution, to the generation of very successful intracellular retrotransposons from ancient retroviruses.
10.1101/gr.073486.107